English Language Speaking Anxiety in Pakistani University Students - Hussain, Syed Qaiser; Fareed, Muhammad; Akhtar, Naeem (International Journal of Psychosocial Rehabilitation, 2020)
English language speaking anxiety is a universal phenomenon. Several studies have been conducted to explore and find out the reasons behind it which unearthed many different aspects of anxiety. The purpose of this study is to find out the levels of speaking anxiety among Pakistani university students and to see if EFL speakers of Pakistan have the same factors of speaking anxiety, as pointed out in the adapted version of Foreign Language Classroom Anxiety Scale (FLCAS). An adapted version of FLCAS was employed to find out the answers to these questions. The sample was taken from a public sector university comprising a total number of 512 students. The results show that, overall, the students have a low level of speaking anxiety and the adapted version of FLCAS does not completely serve the purpose of measuring the level of speaking anxiety in the Pakistani context. From this study it is recommended that a thorough study comprising other disciplines as well must be carried out to find out the factors causing speaking anxiety in Pakistani learners of English as second language.